Topology optimization of heat sinks for instantaneous chip cooling using a transient pseudo-3D thermofluid model. (June 2020) - Zeng, Tao; Wang, Hu; Yang, Mengzhu; Alexandersen, Joe
Highlights: A transient pseudo-3D model is proposed to approximately replace a full 3D model, for cheap optimization. The accuracy of temperature profile of base plate in transient pseudo-3D model is quantitatively measured. A detailed analysis of penalty factors is made for reasonably choosing their values. Instantaneous thermal performance is vastly improved and pumping power consumption is reduced. Abstract: With the increasing power density of electronics components, the heat dissipation capacity of heat sinks gradually becomes a bottleneck. Many structural optimization methods, including topology optimization, have been widely used for heat sinks. Due to its high design freedom, topology optimization is suggested for the design of heat sinks using a transient pseudo-3D thermofluid model to acquire better instantaneous thermal performance. The pseudo-3D model is designed to reduce the computational cost and maintain an acceptable accuracy. The model relies on an artificial heat convection coefficient to couple two layers and establishes the approximate relationship with the corresponding 3D model. In the model, a constant pressure drop and heat generation rate are treated. The material distribution is optimized to reduce the average temperature of the base plate at the prescribed terminal time. Furthermore, to reduce the intermediate density regions during the density-based topology optimization procedure, a detailed analysis of interpolation functions is made and the penalty factors are chosen on this basis. Finally, considering the engineering application of the model, a practical model with a more powerful cooling medium and higher inlet pressure is built. The optimized design shows a better instantaneous thermal performance and provides 66.7% of the pumping power reduction compared with the reference design.